Lived Experiences of Novice Secondary School English Teachers in the Implementation of Modular Distance Learning in the Philippines - Miranda, Criscel C.; Miranda, Khif Muamar M.; Pongos, Leonardo B. (Future Science / FSH-PH Publications, 2024)
As COVID-19 forced schools to shift to distance learning, the modular approach, in particular, became the most viable option for the continuity of learning. However, these sudden changes also brought unique experiences to novice teachers. This study explored the lived experiences of novice secondary school English teachers (NSSET) in Tagum City in implementing modular distance learning (MDL) in the context of the pandemic. Phenomenological inquiry based on Bronfenbrenner's ecological theory was used to explain the experiences of the eight (8) participants. Using validated researcher-made interview questions, virtual in-depth interviews were conducted. Through Braun and Clarke’s (2006) six-step framework, themes that emerged, categorized into five echelons, are as follows: poor cooperation of parents and students, and productive collaboration with colleagues and immediate heads; overwhelming pressure from external sources, and taking direction from others’ influence; perpetual communication breakdown, and confronting challenges in the delivery of modular learning; meeting society’s expectations; abrupt adjustment to the new normal. These shape the experiences of the NSSET in conducting MDL in the new normal. However, the poor cooperation of parents and students poses the most significant experience for the NSSET. Notwithstanding, novice teachers navigated successfully through these experiences brought about by implementing MDL amid the pandemic.